The Existence Of Kampung Pempek 26 Ilir, Palembang South Sumatra 1993-2010 - Destri Ramadhani; Popy Ariska; Syarifuddin; Supriyanto (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2022)
Pempek is a typical Palembang food that has existed since the time of the Sriwijaya Kingdom which is known as kelesan. There is also a Pempek culinary center in Palembang, precisely in Pempek 26 Ilir Village. The subject of this research is the development of Kampung Pempek 26 Ilir Palembang (1993-2010). This paper aims to describe the development of Kampung Pempek 26 Ilir Palembang (1993-2020). The method used to answer this problem is a qualitative research method. The results showed that since 1993 there have been traders who sell pempek in Kampung Pempek 26 Ilir but still few. Over time, more and more people were producing pempek, and in 2005, pempek sellers in the village of Pempek 26 Ilir, Palembang became increasingly crowded and were considered to have sold whole pempek. However, Pempek 26 Ilir Village has not been established as a culinary village, precisely in 2010 Pempek 26 Ilir Village officially became the center of the Pempek Palembang culinary trade. This study uses a qualitative research method with a descriptive approach using four methods, namely observation, interviews, literature study and documentation.